Perancangan Ulang Layout Open Storage Warehouse dengan Metode Systematic Layout Planning dan Class Based Storage - Amalia Putri Abdillah; Fipka Bisono, S,ST.,M.T; Aditya Maharani (Proceedings Conference On Design Manufacture Engineering And Its Application, 2023)
Companies engaged in heavy equipment, both distributors and heavy equipment maintenance processes, generally have warehouses in the storage of spare parts. UT Surabaya has many support points that result in the accumulation of spare parts storage to eat other areas. As a result, the company's workflow is hampered due to improper placement of spareparts in the proper area which results in damage to spare parts. One method that can solve this problem is the Systematic Layout Planning method. This method has a detailed procedure for arranging layouts so that it can bring up more than one alternative layout. In addition, the Class Based Storage method is also used as a design and calculation of racks to design a warehousing system that is aligned within the company. The use of this method resulted in the proposed layout material handling cost, namely the total initial layout OMH was Rp759,235.74, - while the proposed layout OMH was Rp646,000.06,-,. In the comparison of OMH, it was found that the cost decreased by Rp113,235.68,- per day. So the new layout is able to increase the efficiency of mileage material handling costs.